Kebijakan Hukum Pidana Penanganan dan Pengelolaan Sampah Kampanye Dalam Pemilihan Umum Di Indonesia - Aras Firdaus; Qory Rizqiah H Kalingga (Jurnal Ilmiah Penegakan Hukum, 2021)
Environmental problems that are not realized by the Indonesian people are the handling and management of waste during the general election campaign held by legislative candidates and executive candidates in campaigning for themselves in the future government. Piling up garbage at the end of the campaign should be the responsibility of these candidates. This research aims to make strict legal rules and to socialize the regulations that are obeyed by candidates who will campaign in the future so that they can protect the environment. The research method used is normative legal research. This research is descriptive analytical. Data collection techniques are carried out by means of literature study and also by conducting direct interviews with informants. Research Results Show the importance of legal regulations regarding waste management during general election campaigns. So that the environment remains clean and beautiful. The conclusion is to make strict legal rules and so that the parties socialize these regulations are obeyed by candidates who will campaign in the future so that they can preserve the environment